Field/isolated lenticular galaxies with high SN values: the case of NGC 4546 and its globular cluster system - Escudero, Carlos Gabriel (2020)
We present a photometric study of the field lenticular galaxy NGC 4546 using Gemini/GMOS imaging in g′r′i′z′. We perform a 2D image decomposition of the surface brightness distribution of the galaxy using galfit, finding that four components adequately describe it. The subtraction of this model from our images and the construction of a colour map allow us to examine in great detail the asymmetric dust structures around the galactic centre. In addition, we perform a detailed analysis of the globular cluster (GC) system of NGC 4546. Using a Gaussian Mixture Model algorithm in the colour-colour plane we detected hints of multiple groups of GC candidates: the classic blue and red subpopulations, a group with intermediate colours that present a concentrated spatial distribution towards the galaxy, and an additional group towards the red end of the colour distribution. We estimate a total GC population for NGC 4546 of 390 ± 60 members and specific frequency SN = 3.3 ± 0.7, which is relatively high compared to the typical value for galaxies of similar masses and environment. We suggest that the unusual GC population substructures were possibly formed during the interaction that led to the formation of the young ultra-compact dwarf (NGC 4546-UCD1) found in this system. Finally, we estimate the distance modulus of NGC 4546 by analyzing its luminosity function, resulting in (m − M) = 30.75 ± 0.12 mag (14.1 Mpc).